The Contribution of Micro Finance Institutions on the Growth of Small and Medium Business : A Case Study of North Kigezi Diocese Sacco In Rukungiri Municipality. - Ainembabazi, Wensi (Kabale University, 2023)
The study was set to find out the contribution of micro finance institutions mostly (SA CC Os) to the financial performance of small scale enterprises in Uganda while considering a case study of North Kigezi SACCO, found in Rukungiri Municipality and to the neighbouring areas of Kihindi, Kinyasano, Nyakibale, and other divisions. The study used four objectives including; to document the requirements for accessing credit services from SACCOs by small scale enterprises, to find out the challenges faced by small scale enterprises in accessing credits from SACCOs, to identify the possible solutions to the challenges faced by small scale enterprises in accessing credits from SACCOs and to ascertain the relationship between SACCOs and the financial performance of small scale enterprises. The problem statement was lack of access to funds and income opportunities since Small-scale enterprises operate with inadequate capital, (Arkrutoo, 2005). The researcher collected the literature according to the specific objectives of the study. Furthermore, the researcher adopted a case study research design, where North Kigezi SACCO represented the entire country Uganda. The study used a sample size of 86 respondents during data collection from the study area. Data was collected by the use of questionnaires that were both closed and open ended in nature. Findings from the study established that the requirements for accessing credit services from North Kigezi SACCO by small-scale enterprises include; collateral security, being an active member, Local Council letter, and having guarantor, among other requirements. In addition, that lack of collateral security, high-interest rates, lack of debt and equity funds, high level of illiteracy, lack of specialized skills by clients and short loan period repayment period are the challenges faced by small scale enterprise owners in accessing the credit services from the North Kigezi SACCO. Also, that there is a perfect positive linear relationship between financial performance of small business enterprises and North Kigezi SACCO. This was further evidenced by Karl Pearson's correlation Coefficient which was found to be 0.85. The researcher recommended North Kigezi SACCO to reduce on the requirements for loan disbursement, employing highly trained staff, to put in place the necessary infrastructure such as: to start using computers to ensure that its clients find it easy to access services as it was revealed that clients find difficulty in accessing loans from the SACCO, government intervention, advertisement of the SACCO products, training of the employees, and financial literacy is meant for both the borrowers and potential borrowers for managing their finances from SACCOS, are also recommended by the study.